Absence of Adverse Effects on Pulmonary Histopathology and Functions Following Inhalation Exposure to Chloromethylisothiazolinone/Methylisothiazolinone - Sam Kacew; Esref Demir (Toxics)
In South Korea, issues have been raised regarding exposure to humidifier disinfectant products containing certain chemicals postulated to induce lung diseases in consumers. Several rodent studies utilizing whole-body inhalation, which comprises freely moving animals breathing through the nares, and intranasal instillation involving restraint, were conducted by various Korean Governmental Agencies on these products to investigate whether there is a causal relationship between these products and the development of lung diseases. In particular, the humidifier disinfectant product Kathon, containing chloromethylisothiazolinone and methylisothiazolinone (CMIT and MIT), when directly introduced into inhalation chambers at varying concentrations for up to 13 weeks, produced no significant histopathological alterations and no marked changes in pulmonary function parameters. Further, there was no evidence of cytotoxicity; total and differential cell counts did not differ from control. In addition, the levels of cytokine markers of inflammation were not markedly altered. In contrast to published papers utilizing intratracheal and intranasal instillation, where the animal is anesthetized and chemical bypasses the defense mechanisms in the respiratory tract, then reaches the pulmonary region, ignoring recommended dose levels was found to initiate fibrotic responses in mice and rats. However, the usefulness of experimental results to extrapolate to humans obtained following intratracheal and intranasal instillation studies is of limited value because the data generated did not use a realistic design and appropriate dosimetry. Therefore, these findings have significant drawbacks in their use to characterize an inhalation risk for pulmonary fibrosis in humans and cannot be used for the extrapolation of such risk to humans. It is thus evident that the inhalation data generated by the Korean Regulatory Agencies are more realistic and show that exposure to CMIT and MIT does not initiate pulmonary fibrosis. Although inhalation studies still do not fully replicate real-world human exposure scenarios and have limitations for direct extrapolation to humans, they are nevertheless more appropriate than intratracheal or intranasal instillation models.